2012
DOI: 10.1093/cid/cir1053
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review and Survey of Childhood Pneumonia Etiology Studies: 2000–2010

Abstract: The Pneumonia Etiology Research for Child Health (PERCH) project is the largest multicountry etiology study of childhood pneumonia since the Board on Science and Technology in International Development studies of the 1980s. However, it is not the only recent or ongoing pneumonia etiology study, and even with seven sites, it cannot capture all epidemiologic settings in the developing world. Funding providers, researchers and policymakers rely on the best available evidence to strategically plan programs, new re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 83 publications
5
57
0
1
Order By: Relevance
“…Nevertheless data from vaccine-probe studies indicate that the predominant aetiologic agent is Streptococcus pneumoniae , which is estimated to cause 18% of severe cases and 33% of deaths 1 9. Other important vaccine preventable pathogens include Haemophilus influenzae type b (Hib), estimated to account for 4% of severe episodes and 16% of deaths and influenza virus which is associated with approximately 7% of severe episodes and 11% of deaths 1.…”
Section: Childhood Pneumoniamentioning
confidence: 99%
“…Nevertheless data from vaccine-probe studies indicate that the predominant aetiologic agent is Streptococcus pneumoniae , which is estimated to cause 18% of severe cases and 33% of deaths 1 9. Other important vaccine preventable pathogens include Haemophilus influenzae type b (Hib), estimated to account for 4% of severe episodes and 16% of deaths and influenza virus which is associated with approximately 7% of severe episodes and 11% of deaths 1.…”
Section: Childhood Pneumoniamentioning
confidence: 99%
“…Recent systematic reviews of childhood pneumonia etiology suggest that in developing countries, a few bacteria (S. pneumoniae and H. influenzae) and viruses (respiratory syncytial virus, influenza virus) are associated with majority of childhood CAP. 3,5,[10][11][12] A systematic review from India suggested that about 15-24% of bacterial pneumonia in South Asian countries can be attributed to S. pneumonia. 13 Accurate, reliable and rapid determination of etiology in childhood CAP is important because it would influence individual treatment decisions, antibiotic policy in the community, and also rational immunization policy at a national level.…”
mentioning
confidence: 99%
“…Consequently, studies describe different frequency and types of pathogens associated with pneumonia. Recent studies based on modern microbiological diagnostics stated that in more than 25% of children with pneumonia causative agent does not identify; in 25% proved by the viral etiology in 25% of bacterial and 25% of patients have a mixed infection (17). Major viral causes of pneumonia in infants and children include respiratory syncytial virus, influenza, adenoviruses, parainfluenza and human metapneumovirus.…”
Section: Discussionmentioning
confidence: 99%